PERAN POIN TATA KRAMA DALAM ETIKA PARIWARA INDONESIA SEBAGAI INSTRUMEN PERLINDUNGAN KONSUMEN DALAM INDUSTRI PERIKLANAN - Rakha Ariansyah; Muhamad Ghandi Albasyir; Fairuz Zaky Ahmad; Rifandi; Daniel Handoko (Jurnal Riset Multidisiplin Edukasi, 2025)
This research investigates the role of ethical guidelines, specifically the "Tata Krama" (code of conduct) in the Indonesian Advertising Ethics Code (Etika Pariwara Indonesia/EPI) as a protective instrument for consumer rights in the advertising industry. Employing a qualitative descriptive with literature analysis method (library research) which aims to study in depth the contents of the Indonesian Advertising Ethics Amendment 2020 document as the main source, particularly clauses under Article III concerning advertising content. The research highlights how ethical provisions on misleading information, exaggeration (hyperbolization), testimonials, and child-targeted advertising serve as safeguards for consumers. The findings suggest that the Tata Krama in EPI plays a crucial normative role, both in guiding industry conduct and as a self-regulatory framework that complements state regulations. This study contributes to media and advertising ethics education and provides a reference for future studies concerning media responsibility and consumer protection.